Seasonality of pathogens causing community‐acquired pneumonia. Issue 4 (17th January 2017) - Cilloniz, Catia; Ewig, Santiago; Gabarrus, Albert; Ferrer, Miquel; Puig de la Bella Casa, Jorge; Mensa, Josep; Torres, Antoni
ABSTRACT: Background and objective: Seasonal distribution of microbial aetiology in patients with community‐acquired pneumonia (CAP) may add important information both for epidemiologists and clinicians. We investigate the seasonal distribution of microbial aetiology in CAP. Methods: This prospective observational study was carried out in the Hospital Clinic of Barcelona, Spain (January 2003–December 2014). Results: We studied 4431 patients with CAP, of whom 2689 (61%) were males. Microbial aetiology was identified in 1756 patients (40%). CAP was most frequent in winter (34%) but two‐third of patients with CAP presented in other seasons. Seasonal variations included Streptococcus pneumoniae (winter 21% vs spring 17% vs summer 14% vs autumn 13%, overall P < 0.001). Influenza viruses were most prevalent in autumn (6%) and winter (5%) compared with spring (3%) and summer (1%) (overall P < 0.001). Legionella pneumophila was most frequent in autumn (4%) and summer (4%) compared with spring (2%) and winter (1%) (overall P < 0.001). Incidence of polymicrobial pneumonia also differed between seasons (winter 7% vs spring 5% vs summer 3% vs autumn 6%, overall P = 0.001). We observed a significant correlation between the lowest seasonal average temperature and polymicrobial pneumonia, pneumococcal pneumonia, and influenza viruses; conversely, L. pneumophila was more common when temperatures were higher. Conclusion: CAP should not be regarded as a seasonal disease but occurs throughout all seasons. However, S. pneumoniae, influenza viruses, polymicrobial pneumonia and L. pneumophila are clearly subject to seasonal variations. Abstract : Seasonal variations of microbial aetiology may be important for future community‐acquired pneumonia (CAP) recommendations. CAP should not be regarded as a seasonal disease, as it occurs throughout all seasons. However, Streptococcus pneumoniae, respiratory viruses, polymicrobial pneumonia and Legionella pneumophila are clearly subject to seasonal variations.